P612 Lower incidence of COVID-19 in patients with Inflammatory Bowel Diseases treated with non-gut-selective biologic therapy: an observational multicentre study. (27th May 2021) - Ferretti, F; Monico, M C; Carvalhas Gabrielli, A M; Carmagnola, S; Bezzio, C; Saibeni, S; Bosani, M; Caprioli, F; Mazza, S; Casini, V; Cortelezzi, C; Parravicini, M; et al.
Abstract: Background: Since the outbreak of COVID-19, concerns have been raised as to whether IBD patients under biologic therapy might be more susceptible to the disease and its complications. This study aimed to determine the incidence and outcomes of COVID-19 in a large cohort of IBD patients on biologic therapy in Lombardy, the hardest-hit Italian region by the pandemic. Methods: This is an observational retrospective multicentre study collecting data about COVID-19 in IBD patients on biologic therapy in regular clinical follow-up at 11 IBD referral units in Lombardy, between February 20th and May 20th, 2020. The main endpoints were to assess the cumulative incidence of COVID-19 and its outcome (hospitalization/death) among IBD patients on biologic therapy and to identify any variations among the different classes of biologic agents. Secondarily, we compared the results with the incidence of COVID-19 in the general population of Lombardy in the same period and the incidence of symptoms suggestive of COVID-19 in our study population compared with those of a second cohort of IBD patients undergoing non-biological therapies and coming from the same geographic area. Results: Overall, 1816 IBD patients on biologic therapy were enrolled. The cumulative incidence of COVID-19 was 3.9 per 1000 (7/1816) with a hospitalization rate of 57% and a case-fatality rate (CFR) of 29%. In our Cohort, the gut-selective therapy (Vedolizumab and Etrolizumab) was the only risk factor of developing symptomatic COVID-19 (OR 8.7, 95% CI 1.7–45.0, p = 0.01). Conversely, non-gut selective anti-cytokine agents were associated with a lower incidence of infection (OR 0.13, 95%CI 0.02–0.74) and development of symptoms (OR 0.60, 95%CI 0.37–0.98). Compared to the general population of Lombardy, a lower incidence of COVID-19 was observed (3.9 vs 8.5 per 1000 with a RR 0.45, 95%CI 0.21–0.95); conversely, in terms of hospitalization rate and CFR, the clinical outcome was not statistically different. Finally, compared to a second cohort of 565 IBD patients treated with non-biologic conventional therapies, a significantly lower risk of symptomatic disease was observed in patients on biologic agents (OR 0.3, 95%CI 0.2–0.4, p<0.01). Conclusion: Compared to the general population, IBD patients on biologic therapy are not exposed to a higher risk of COVID-19; compared to gut-selective agents, cytokine blockers are associated with a lower incidence of symptomatic infection, supporting the decision of maintaining the ongoing treatment.